Current Applications of Ultrasound Imaging in the Preoperative Planning of DIEP Flaps - Perez-Iglesias, Carolina Torres; Laikhter, Elizabeth; Kang, Christine O.; Nassar, Amer H.; Maselli, Amy M.; Cauley, Ryan; Lee, Bernard T. (Journal of Reconstructive Microsurgery, 2022)
Background The deep inferior epigastric artery perforator (DIEP) flap has become the gold standard for autologous breast reconstruction at many institutions. Although the deep inferior epigastric artery displays significant anatomic variability in its intramuscular course, branching pattern and location of perforating vessels, the ability to preoperatively visualize and map relevant vascular anatomy has increased the efficiency, safety and reliability of the DIEP flap. While computed tomography angiography (CTA) is often cited as the preoperative imaging modality of choice for perforator flaps, more recent advances in ultrasound technology have made it an increasingly attractive alternative.Methods An extensive literature review was performed to identify the most common applications of ultrasound technology in the preoperative planning of DIEP flaps.Results This review demonstrated that multiple potential uses for ultrasound technology in DIEP flap reconstruction including preoperative perforator mapping, evaluation of the superficial inferior epigastric system and as a potential adjunct in flap delay procedures. Available studies suggest that ultrasound compares favorably to other widely-used imaging modalities for these indications.Conclusion This article presents an in-depth review of the current applications of ultrasound in the preoperative planning of DIEP flaps and explores some potential areas for future investigation.
Keywords: ultrasonography; duplex ultrasonography; DIEP flap; breast reconstruction; preoperative planning